Halogen-free flame-retardant polypropylene material and its application in water supply and drainage pipes

CN122878673APending Publication Date: 2026-10-09JINGJIANG HAIHONG PLASTIC TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611384011.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-08
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0004]然而,上述方案中,其阻燃体系以铝磷酸盐及ZnMgAl-LDHs等刚性无机粒子为主,粒子表面为高模量无机界面,与聚丙烯基体之间模量差异较大

Benefits of technology

[0032]1、本发明制备的无卤阻燃聚丙烯材料,通过铈负载聚多巴胺包覆聚磷酸铵阻燃剂与丁香酚改性聚硅氧烷的配合使用,构建高效成炭与界面柔顺的阻燃增韧体系。聚多巴胺包覆层在燃烧时作为碳源与聚磷酸铵分解释放的磷酸共同促进致密炭层的形成,并为铈的负载提供配位结合位点,使铈负载于包覆层表面,在不屏蔽聚磷酸铵酸源释放的前提下催化炭层石墨化致密化,协同进行阻燃,同时丁香酚改性聚硅氧烷通过端基酚羟基与聚多巴胺包覆层之间的氢键作用集中在阻燃粒子表面,其聚硅氧烷主链在刚性阻燃粒子与聚丙烯基体之间形成柔性界面层,减少应力集中,使材料在低烟无卤特性下,改善阻燃剂与聚丙烯基体之间的界面相容性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application discloses a kind of halogen-free flame-retardant polypropylene material and its application in water supply and drainage pipe, belong to flame-retardant polypropylene material technical field, first utilize dopamine oxidation self-polymerization on the surface of ammonium polyphosphate and form polydopamine coating layer, then in situ co-precipitation loading cerium, obtain cerium loading polydopamine coated ammonium polyphosphate flame retardant, hydrogen-terminated silicone oil is reacted with eugenol by hydrosilylation, and eugenol-modified polysiloxane is obtained, and polypropylene resin, ethylene-octene copolymer, maleic anhydride grafted polypropylene, cerium loading polydopamine coated ammonium polyphosphate flame retardant, eugenol-modified polysiloxane and additives are melt blended, extruded and granulated to obtain halogen-free flame-retardant polypropylene material, which is used for extrusion molding into water supply and drainage pipe. By constructing efficient charring, flexible interface layer and rubber dispersion phase synergistic flame-retardant toughening system, the pipe maintains good halogen-free flame-retardant and low-temperature impact resistance in cold region low temperature and vibration impact working conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of flame-retardant polypropylene materials, specifically a halogen-free flame-retardant polypropylene material and its application in water supply and drainage pipes. Background Technology

[0002] In shipboard water supply and drainage systems, traditional steel pipes have long faced corrosion problems due to the high humidity and salt spray environment, resulting in high maintenance costs and limited service life. Polypropylene pipes, due to their lightweight, chemical corrosion resistance, rust resistance, ease of processing, and cost advantages, are gradually replacing steel pipes in shipboard water supply and drainage systems. However, polypropylene itself has a low oxygen index and is flammable; therefore, when used in shipboard water supply and drainage pipes, it needs to be endowed with halogen-free flame-retardant properties to meet the low smoke and low toxicity requirements for shipboard fire safety.

[0003] In the prior art, Chinese patent application CN114410008A discloses a non-halogen flame-retardant polypropylene pipe. This pipe uses polypropylene as the matrix, compounded with maleic anhydride-grafted polypropylene, aluminophosphate non-halogen flame retardant, and ZnMgAl-LDHs compounds, and is prepared by compounding and extrusion molding. This method utilizes the mechanism of aluminophosphate flame retardant forming a dense char layer at high temperatures, thereby improving the halogen-free flame-retardant performance of the polypropylene pipe.

[0004] However, the flame-retardant system in the aforementioned schemes is mainly composed of rigid inorganic particles such as aluminophosphates and ZnMgAl-LDHs. The particle surface is a high-modulus inorganic interface, resulting in a significant modulus difference between the particles and the polypropylene matrix. When ships navigate in high-latitude, cold regions, they are exposed to low temperatures for extended periods. The vibrations and impacts during navigation also cause these rigid particles to easily become stress concentration points, leading to microcracks in the pipe wall. These cracks thin the wall, creating preferential channels for flame penetration and causing localized failure of the flame-retardant barrier. This negatively impacts the long-term flame-retardant reliability and service safety of the ship's water supply and drainage pipes. Therefore, significantly improving the low-temperature impact toughness of flame-retardant polypropylene materials while ensuring halogen-free flame-retardant efficiency has become a pressing technical problem in the field of marine water supply and drainage pipes. Summary of the Invention

[0005] The purpose of this invention is to provide a halogen-free flame-retardant polypropylene material and its application in water supply and drainage pipes. By synergistically introducing cerium-loaded polydopamine-coated ammonium polyphosphate flame retardant and eugenol-modified polysiloxane into the polypropylene matrix, the former, after organic coating with polydopamine and cerium loading, synergistically promotes the formation of a dense graphitized carbon layer during combustion, constructing a synergistic flame-retardant system. The latter, through hydrogen bonding between the terminal phenolic hydroxyl groups and the polydopamine coating layer, accumulates on the surface of the flame retardant. The flexibility of the polysiloxane backbone forms a flexible interface layer between the rigid flame-retardant particles and the polypropylene matrix, providing interfacial stress buffering. Combined with the toughening of the ethylene-octene copolymer bulk rubber and the dispersion bridging of maleic anhydride-grafted polypropylene, the material achieves a significant improvement in low-temperature impact toughness while ensuring halogen-free flame-retardant efficiency and low-smoke characteristics, meeting the flame-retardant reliability and service safety requirements of marine water supply and drainage pipes under cold, low-temperature, and vibration-impact conditions.

[0006] The objective of this invention can be achieved through the following technical solutions:

[0007] This invention provides a halogen-free flame-retardant polypropylene material, comprising the following raw materials by weight:

[0008] 300-500 parts of polypropylene resin;

[0009] 30-60 parts of ethylene-octene copolymer;

[0010] 10-20 parts of maleic anhydride-grafted polypropylene;

[0011] Eugenol-modified polysiloxane 10-25 parts;

[0012] 40-60 parts of cerium-loaded polydopamine-coated ammonium polyphosphate flame retardant;

[0013] Antioxidant 1010: 0.5-1 part;

[0014] Antioxidant 168, 0.5-1 part;

[0015] Calcium stearate 1-3 parts.

[0016] The specific preparation process of the above-mentioned halogen-free flame-retardant polypropylene material is as follows:

[0017] Polypropylene resin, ethylene-octene copolymer, maleic anhydride-grafted polypropylene, cerium-loaded polydopamine-coated ammonium polyphosphate flame retardant, antioxidant 1010, antioxidant 168 and calcium stearate are placed in a mixer and mixed at 300-500 r / min for 5-10 min. The mixed material is then fed into a twin-screw extruder through the main feed port. Eugenol-modified polysiloxane is injected through the side feed port. After melt blending and extrusion, the material is cooled and pelletized to obtain halogen-free flame-retardant polypropylene material.

[0018] The aforementioned twin-screw extruder has four sections with temperature settings of 170-180℃, 180-190℃, 190-200℃, and 195-205℃, respectively. The die head temperature is 190-200℃, and the screw speed is 200-300 r / min.

[0019] Furthermore, the specific preparation process of eugenol-modified polysiloxane is as follows:

[0020] Hydrogen-containing silicone oil and eugenol were placed in a reactor equipped with a condenser and stirred at 25-35℃ for 10-20 min. Karstedt platinum catalyst was added under a nitrogen atmosphere, and the temperature was raised to 90-100℃ for 6-8 h. The reaction solution was then distilled under reduced pressure to constant weight to obtain eugenol-modified polysiloxane.

[0021] The ratio of the above-mentioned hydrogen-containing silicone oil, eugenol and Karstedt platinum catalyst is 20-40g: 2-4g: 0.1-0.2mL.

[0022] Furthermore, the specific preparation process of the cerium-supported polydopamine-coated ammonium polyphosphate flame retardant is as follows:

[0023] Cerium nitrate hexahydrate, anhydrous ethanol, and deionized water were placed in a reaction vessel and stirred at 25-35℃ for 40-60 min. Polydopamine-coated ammonium polyphosphate was added and stirred at 40-45℃ for 1-2 h. Ammonia water with a concentration of 1 mol / L was added to adjust the pH of the reaction solution to 9.0-10.5, and stirring was continued for 1-2 h. The mixture was allowed to stand at 45-55℃ for 6-8 h, filtered, washed, and freeze-dried to constant weight to obtain cerium-loaded polydopamine-coated ammonium polyphosphate flame retardant.

[0024] The ratio of the above-mentioned cerium nitrate hexahydrate, anhydrous ethanol, deionized water and polydopamine-coated ammonium polyphosphate is 35-50g: 200-300mL: 1-1.5L: 60-80g.

[0025] Furthermore, the specific preparation process of polydopamine-coated ammonium polyphosphate is as follows:

[0026] Dopamine hydrochloride, ammonium polyphosphate, and deionized water were placed in a reaction vessel and stirred at 25-35℃ for 10-20 min. A Tris-HCl buffer solution with a pH of 8.5 was added, and a 0.5 mol / L sodium hydroxide solution was added to adjust the pH of the reaction solution to 8.5-9.0. The reaction was carried out at 20-30℃ for 22-24 h. After centrifugation, washing, and vacuum drying to constant weight, polydopamine-coated ammonium polyphosphate was obtained.

[0027] The ratio of the above-mentioned dopamine hydrochloride, ammonium polyphosphate, deionized water and Tris-HCl buffer solution is 20-25g: 80-100g: 1-1.2L: 80-120mL.

[0028] This invention also provides an application of halogen-free flame-retardant polypropylene material in water supply and drainage pipes, the specific preparation process of which is as follows:

[0029] After drying, the halogen-free flame-retardant polypropylene material is melted and plasticized by a single-screw extruder and extruded into a pipe blank by the die head. The pipe blank is then subjected to vacuum sizing, spray cooling, traction, and cutting to obtain water supply and drainage pipe materials.

[0030] The above-mentioned single-screw extruder has four sections with temperature settings of 170-180℃, 180-190℃, 190-200℃, and 195-205℃, respectively. The die head temperature is 190-200℃, and the screw speed is 30-50 r / min.

[0031] The beneficial effects of this invention are:

[0032] 1. The halogen-free flame-retardant polypropylene material prepared by this invention utilizes a combination of cerium-loaded polydopamine-coated ammonium polyphosphate flame retardant and eugenol-modified polysiloxane to construct a highly efficient char-forming and interface-compliant flame-retardant and toughening system. During combustion, the polydopamine coating acts as a carbon source, working in conjunction with the phosphoric acid released from the decomposition of ammonium polyphosphate to promote the formation of a dense char layer and providing coordination sites for cerium loading. This allows cerium to be loaded onto the surface of the coating layer, catalyzing the graphitization and densification of the char layer without shielding the release of the ammonium polyphosphate acid source, thus synergistically enhancing flame retardancy. Simultaneously, the eugenol-modified polysiloxane concentrates on the surface of the flame-retardant particles through hydrogen bonding between the terminal phenolic hydroxyl groups and the polydopamine coating layer. Its polysiloxane backbone forms a flexible interface layer between the rigid flame-retardant particles and the polypropylene matrix, reducing stress concentration and improving the interfacial compatibility between the flame retardant and the polypropylene matrix while maintaining low smoke and halogen-free characteristics.

[0033] 2. The halogen-free flame-retardant polypropylene material prepared by this invention uses block copolymer polypropylene as the matrix, combined with cerium-loaded polydopamine-coated ammonium polyphosphate flame retardant, eugenol-modified polysiloxane, ethylene-octene copolymer, and maleic anhydride-grafted polypropylene. It exhibits a synergistic effect of low-temperature impact resistance and flame-retardant reliability under cold and vibration-impact conditions. Maleic anhydride-grafted polypropylene promotes the uniform dispersion of the flame retardant in the polypropylene matrix; the rubber dispersion phase formed by the ethylene-octene copolymer absorbs and disperses impact energy through elastic deformation under impact loads, inhibiting crack initiation; the flexible interface layer formed by the eugenol-modified polysiloxane and flame-retardant particles buffers the modulus difference between the rigid flame-retardant particles and the matrix, mutually promoting the inhibition of microcrack propagation with the rubber dispersion phase, reducing the risk of pipe wall cracking and forming a flame penetration channel under low-temperature impact, and ensuring the low-temperature impact resistance and flame-retardant barrier integrity of the pipe material. Detailed Implementation

[0034] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0035] Example 1: This example provides a halogen-free flame-retardant polypropylene material, prepared through the following steps:

[0036] S1: Place 20g of dopamine hydrochloride, 80g of ammonium polyphosphate and 1L of deionized water in a reaction vessel, stir at 200r / min for 10min at 25℃, add 80mL of Tris-HCl buffer solution with pH 8.5, and add 0.5mol / L sodium hydroxide solution to adjust the pH of the reaction solution to 8.5. React at the same stirring rate at 20℃ for 22h. After the reaction is completed, centrifuge to remove the supernatant, add deionized water and centrifuge twice, collect the precipitate and vacuum dry at 60℃ to constant weight to obtain polydopamine-coated ammonium polyphosphate.

[0037] This step involves preparing polydopamine-coated ammonium polyphosphate via oxidative self-polymerization. Under weakly alkaline conditions, dopamine molecules released after deprotonation of dopamine hydrochloride undergo intramolecular cyclization, rearrangement, and oxidative polymerization to form polydopamine oligomers. The catechol hydroxyl and amino groups in the polydopamine molecular chain are adsorbed onto the surface of ammonium polyphosphate through hydrogen bonding and electrostatic interactions, and are deposited and solidified in situ on the surface through intermolecular π-π stacking and oxidative crosslinking to form a polydopamine coating layer, thus obtaining polydopamine-coated ammonium polyphosphate.

[0038] S2: Place 35g of cerium nitrate hexahydrate, 200mL of anhydrous ethanol and 1L of deionized water in a reaction vessel, stir at 200r / min for 40min at 25℃, add 60g of polydopamine-coated ammonium polyphosphate, stir at the same stirring rate at 40℃ for 1h, add 1mol / L ammonia water to adjust the pH of the reaction solution to 9.0, continue stirring for 1h, let stand at 45℃ for 6h, after the reaction is completed, cool to room temperature, filter, wash the solid twice with deionized water and anhydrous ethanol, freeze dry to constant weight to obtain cerium-loaded polydopamine-coated ammonium polyphosphate flame retardant.

[0039] This step involves preparing cerium-supported polydopamine-coated ammonium polyphosphate via ion coordination and in-situ co-precipitation. Under alkaline conditions, Ce... 3+ Hydrolysis and precipitation produce cerium hydroxide. The coordination between the amino and catechol groups in the polydopamine layer and cerium ions induces cerium species to nucleate heterogeneously on the surface of the polydopamine layer and grow anchored. After aging, a cerium-based deposition layer is formed, resulting in a cerium-loaded polydopamine-coated ammonium polyphosphate flame retardant.

[0040] S3: 20g of hydrogen-containing silicone oil and 2g of eugenol were placed in a reactor equipped with a condenser and stirred at 200r / min for 10min at 25℃. 0.1mL of Karstedt platinum catalyst was added under a nitrogen atmosphere, and the temperature was raised to 90℃ and stirred at 300r / min for 6h. After the reaction was completed, the mixture was cooled to room temperature and the reaction solution was distilled under reduced pressure at -0.09MPa to constant weight to obtain eugenol-modified polysiloxane.

[0041] This step involves the preparation of eugenol-modified polysiloxanes via platinum-catalyzed hydrosilylation. Under the action of a Karstedt platinum catalyst, the Si-H bonds at the ends of the hydrogen-terminated silicone oil molecular chains undergo a hydrosilylation reaction with the allyl double bonds in the eugenol molecule, grafting eugenol onto the ends of the polysiloxane molecular chains. This addition reaction exhibits high chemoselectivity for carbon-carbon double bonds, allowing the phenolic hydroxyl groups of eugenol to be retained during the reaction, thus yielding eugenol-modified polysiloxanes.

[0042] S4: Place 300g of polypropylene resin, 30g of ethylene-octene copolymer, 10g of maleic anhydride-grafted polypropylene, 40g of cerium-loaded polydopamine-coated ammonium polyphosphate flame retardant, 0.5g of antioxidant 1010, 0.5g of antioxidant 168, and 1g of calcium stearate (lubricant) in a mixer and mix at 300r / min for 5min. Add the mixed material to a twin-screw extruder through the main feed port. Inject 10g of eugenol-modified polysiloxane through the side feed port. The processing temperatures of the twin-screw extruder are 170℃, 180℃, 190℃, and 195℃, with a die head temperature of 190℃ and a screw speed of 200r / min. After melt blending and extrusion, the material is cooled and pelletized to obtain halogen-free flame-retardant polypropylene material.

[0043] Example 2: This example provides a halogen-free flame-retardant polypropylene material, prepared through the following steps:

[0044] S1: 23g of dopamine hydrochloride, 90g of ammonium polyphosphate and 1.1L of deionized water were placed in a reaction vessel and stirred at 250r / min for 15min at 30℃. 100mL of Tris-HCl buffer solution with a pH of 8.5 was added, and sodium hydroxide solution with a concentration of 0.5mol / L was added to adjust the pH of the reaction solution to 8.8. The reaction was carried out at 25℃ with the same stirring rate for 23h. After the reaction was completed, the supernatant was removed by centrifugation, and the mixture was washed three times by centrifugation with deionized water. The precipitate was collected and vacuum dried at 65℃ to constant weight to obtain polydopamine-coated ammonium polyphosphate.

[0045] S2: 42g of cerium nitrate hexahydrate, 250mL of anhydrous ethanol and 1.2L of deionized water were placed in a reaction vessel and stirred at 250r / min for 50min at 30℃. 70g of polydopamine-coated ammonium polyphosphate was added and stirred at the same stirring rate at 42℃ for 1.5h. Ammonia water with a concentration of 1mol / L was added to adjust the pH of the reaction solution to 10, and stirring was continued for 1.5h. The mixture was then allowed to stand at 50℃ for 7h. After the reaction was completed, the mixture was cooled to room temperature, filtered, and the solid was washed three times with deionized water and anhydrous ethanol. The solid was then freeze-dried to constant weight to obtain cerium-loaded polydopamine-coated ammonium polyphosphate flame retardant.

[0046] S3: 30g of hydrogen-containing silicone oil and 3g of eugenol were placed in a reactor equipped with a condenser and stirred at 250r / min for 15min at 30℃. 0.15mL of Karstedt platinum catalyst was added under a nitrogen atmosphere, and the temperature was raised to 95℃ and stirred at 350r / min for 7h. After the reaction was completed, the mixture was cooled to room temperature and the reaction solution was distilled under reduced pressure at -0.09MPa to constant weight to obtain eugenol-modified polysiloxane.

[0047] S4: Place 400g of polypropylene resin, 45g of ethylene-octene copolymer, 15g of maleic anhydride-grafted polypropylene, 50g of cerium-loaded polydopamine-coated ammonium polyphosphate flame retardant, 0.8g of antioxidant 1010, 0.8g of antioxidant 168, and 2g of calcium stearate (lubricant) in a mixer and mix at 400r / min for 8min. Add the mixed material to a twin-screw extruder through the main feed port. Inject 17g of eugenol-modified polysiloxane through the side feed port. The processing temperatures of the twin-screw extruder are 175℃, 185℃, 195℃, and 200℃, the die head temperature is 195℃, and the screw speed is 250r / min. After melt blending and extrusion, the material is cooled and pelletized to obtain halogen-free flame-retardant polypropylene material.

[0048] Example 3: This example provides a halogen-free flame-retardant polypropylene material, prepared through the following steps:

[0049] S1: 25g of dopamine hydrochloride, 100g of ammonium polyphosphate and 1.2L of deionized water were placed in a reaction vessel and stirred at 300r / min for 20min at 35℃. 120mL of Tris-HCl buffer solution with a pH of 8.5 was added, and sodium hydroxide solution with a concentration of 0.5mol / L was added to adjust the pH of the reaction solution to 9.0. The reaction was carried out at 30℃ with the same stirring rate for 24h. After the reaction was completed, the supernatant was removed by centrifugation, and the mixture was washed 4 times by centrifugation with deionized water. The precipitate was collected and vacuum dried at 70℃ to constant weight to obtain polydopamine-coated ammonium polyphosphate.

[0050] S2: Place 50g of cerium nitrate hexahydrate, 300mL of anhydrous ethanol and 1.5L of deionized water in a reaction vessel, stir at 300r / min for 60min at 35℃, add 80g of polydopamine-coated ammonium polyphosphate, stir at the same stirring rate at 45℃ for 2h, add 1mol / L ammonia water to adjust the pH of the reaction solution to 10.5, continue stirring for 2h, let stand at 55℃ for 8h, after the reaction is completed, cool to room temperature, filter, wash the solid 4 times with deionized water and anhydrous ethanol, freeze dry to constant weight to obtain cerium-loaded polydopamine-coated ammonium polyphosphate flame retardant.

[0051] S3: 40g of hydrogen-containing silicone oil and 4g of eugenol were placed in a reactor equipped with a condenser and stirred at 300r / min for 20min at 35℃. 0.2mL of Karstedt platinum catalyst was added under a nitrogen atmosphere, and the temperature was raised to 100℃ and stirred at 400r / min for 8h. After the reaction was completed, the mixture was cooled to room temperature and the reaction solution was distilled under reduced pressure at -0.09MPa to constant weight to obtain eugenol-modified polysiloxane.

[0052] S4: Place 500g of polypropylene resin, 60g of ethylene-octene copolymer, 20g of maleic anhydride-grafted polypropylene, 60g of cerium-loaded polydopamine-coated ammonium polyphosphate flame retardant, 1g of antioxidant 1010, 1g of antioxidant 168 and 3g of calcium stearate (lubricant) in a mixer and mix at 500r / min for 10min. Add the mixed material to a twin-screw extruder through the main feed port. Inject 25g of eugenol-modified polysiloxane through the side feed port. The processing temperatures of the twin-screw extruder are 180℃, 190℃, 200℃, 205℃, and the die head temperature is 200℃. The screw speed is 300r / min. After melt blending and extrusion, the material is cooled and pelletized to obtain halogen-free flame-retardant polypropylene material.

[0053] Example 4: This example provides an application of halogen-free flame-retardant polypropylene material in water supply and drainage pipes, including the following steps:

[0054] The halogen-free flame-retardant polypropylene material granules prepared in Example 1 were dried at 80°C for 2 hours and then extruded using a single-screw extruder. The temperatures of the four temperature zones of the extruder were 170°C, 180°C, 190°C, and 195°C, respectively. The die head temperature was 190°C, and the screw speed was 30 r / min. The melt extrusion formed a pipe blank, which was then subjected to vacuum sizing, spray cooling, traction, and cutting to obtain water supply and drainage pipe materials.

[0055] Example 5: This example provides an application of halogen-free flame-retardant polypropylene material in water supply and drainage pipes, including the following steps:

[0056] The halogen-free flame-retardant polypropylene material granules prepared in Example 2 were dried at 80°C for 2 hours and then extruded using a single-screw extruder. The extruder temperature zones were 175°C, 185°C, 195°C, and 200°C, with a die head temperature of 195°C and a screw speed of 40 r / min. The melt extrusion formed a pipe blank, which was then subjected to vacuum sizing, spray cooling, traction, and cutting to obtain water supply and drainage pipe materials.

[0057] Example 6: This example provides an application of halogen-free flame-retardant polypropylene material in water supply and drainage pipes, including the following steps:

[0058] The halogen-free flame-retardant polypropylene material granules prepared in Example 3 were dried at 80°C for 2 hours and then extruded using a single-screw extruder. The extruder temperature zones were 180°C, 190°C, 200°C, and 205°C, the die head temperature was 200°C, and the screw speed was 50 r / min. The melt extrusion formed a pipe blank, which was then subjected to vacuum sizing, spray cooling, traction, and cutting to obtain water supply and drainage pipe materials.

[0059] The nominal outer diameter of the water supply and drainage pipes prepared in Examples 4-6 above is dn75mm, and the nominal wall thickness is 2.3mm.

[0060] Comparative Example 1: The difference from Example 2 is that in step S4, commercially available ammonium polyphosphate is used instead of the cerium-loaded polydopamine-coated ammonium polyphosphate flame retardant prepared in step S2, while the other steps remain unchanged, to prepare a halogen-free flame-retardant polypropylene material, and this material is used to prepare water supply and drainage pipes in accordance with the method of Example 4.

[0061] Comparative Example 2: The difference from Example 2 is that in step S4, the polydopamine-coated ammonium polyphosphate prepared in step S1 is used instead of the cerium-loaded polydopamine-coated ammonium polyphosphate flame retardant prepared in step S2. The other steps remain unchanged, and a halogen-free flame-retardant polypropylene material is prepared. This material is then used to prepare water supply and drainage pipes in accordance with the method of Example 4.

[0062] Comparative Example 3: The difference from Example 2 is that in step S4, commercially available hydrogen-containing silicone oil is used instead of the eugenol-modified polysiloxane prepared in step S3, while the other steps remain unchanged, to prepare a halogen-free flame-retardant polypropylene material, and this material is used to prepare water supply and drainage pipes in accordance with the method of Example 4.

[0063] Comparative Example 4: The difference from Example 2 is that in step S4, the eugenol-modified polysiloxane prepared in step S3 is removed and replaced with an equal amount of polypropylene resin, while the other steps remain unchanged, to prepare a halogen-free flame-retardant polypropylene material, and this material is used to prepare water supply and drainage pipes in accordance with the method of Example 4.

[0064] The polypropylene resin used in the above examples and comparative examples was block copolymer polypropylene produced by Sinopec Zhenhai Refining & Chemical Co., Ltd., with a melt flow rate of 0.5 g / 10 min and an ethylene content of 10 wt%; the ethylene-octene copolymer (POE) was produced by Dow Chemical, with the grade Engage 8150 and a melt flow rate of 0.5 g / 10 min; the maleic anhydride grafted polypropylene (PP-g-MAH) was produced by Ningbo Nengzhiguang New Material Technology Co., Ltd., with a grafting rate of 1.2 wt%; the ammonium polyphosphate (APP) was type II ammonium polyphosphate produced by Hangzhou Jiersi Flame Retardant Chemical Co., Ltd., with a degree of polymerization >1000; the hydrogen-terminated silicone oil was hydrogen-terminated polydimethylsiloxane produced by Jiangxi Lanxing Xinghuo Organosilicon Co., Ltd., with a hydrogen content of 0.05 wt% and a viscosity of 50 mPa·s; and the Tris-HCl buffer solution was produced by Shanghai Sangon Biotech Co., Ltd., with a concentration of 10 mmol / L and a pH of 8.5.

[0065] The halogen-free flame-retardant polypropylene materials prepared in Examples 1-3 and Comparative Examples 1-4 were subjected to performance tests, and the test results are shown in Table 1.

[0066] Sample preparation: The halogen-free flame-retardant polypropylene materials prepared in the examples and comparative examples were scaled up and prepared by injection molding machine to form standard samples. The injection-molded samples were placed in an environment of (23±2)℃ and (50±5)% relative humidity for 24 hours for later use.

[0067] Tensile properties: In accordance with standard GB / T 1040.2-2022 "Determination of tensile properties of plastics - Part 2: Test conditions for molded and extruded plastics", type 1A dumbbell specimens were used and universal electronic testing machine was used for testing. The tensile strength and elongation at break of the specimens were recorded.

[0068] Flame retardancy test: Refer to standard GB / T 2408-2008 "Determination of flammability of plastics by horizontal and vertical methods" and use the vertical burning method to test and record the flammability rating of the sample (classified as V-0, V-1, V-2), where V-0 represents the best flame retardant effect.

[0069] Referring to the standard GB / T 8323.2-2008 "Plastics Smoke Generation Part 2: Determination of Smoke Density by Single Chamber Method", the test was conducted at a radiant heat flux of 25 kW / m², and the maximum smoke density was recorded. The smaller the maximum smoke density, the lower the smoke production during material combustion, and the better the low-smoke safety.

[0070] Impact resistance: Referencing standard GB / T 1043.1-2008 "Determination of impact properties of simply supported beams of plastics - Part 1: Non-instrumental impact test", a pendulum-type simply supported beam impact testing machine was used for testing. The notched impact strength of the specimen was recorded. Then, the type A notched specimen was placed in a low temperature environment of (-20±2)℃ for 4 hours. After being removed, the impact test was carried out again within 5 seconds, and the notched impact strength of the low temperature specimen was recorded. The higher the notched impact strength, the better the low temperature impact toughness of the material.

[0071] Table 1 Performance Test Table of Halogen-Free Flame-Retardant Polypropylene Materials

[0072]

[0073] The water supply and drainage pipes prepared in Examples 4-6 and Comparative Examples 1-4 were subjected to performance tests, and the test results are shown in Table 2.

[0074] Drop hammer impact test: Referring to standard GB / T 14152-2001 "Test Method for Impact Resistance of Thermoplastic Pipes - Clockwise Rotation Method", 200mm diameter samples were cut from the pipe and conditioned for 2 hours at (23±2)℃ and (-20±2)℃ respectively. A drop hammer of specified mass was then dropped freely from a specified height to impact the pipe. Ten samples were used per group, with each sample impacted once. The number of fractures was recorded. A lower number of fractures indicates better impact resistance of the pipe.

[0075] Table 2 Performance Test Table for Water Supply and Drainage Pipes

[0076]

[0077] As shown in Tables 1 and 2, the halogen-free flame-retardant polypropylene materials and water supply and drainage pipes prepared in Examples 1-3 and Examples 4-6 all achieved a V-0 flammability rating, and their maximum smoke density was lower than that of Comparative Examples 1-4. Compared with the comparative examples, Example 2 showed superior low-temperature notched impact strength, elongation at break, and low-temperature drop hammer impact performance. This invention demonstrates that the flame retardant prepared by organically coating polydopamine and supporting cerium catalyst, in conjunction with the eugenol-modified polysiloxane interfacial flexibility layer and the ethylene-octene copolymer bulk toughening, constructs a uniformly dispersed, gradient-transition interfacial modulus, and stress-dissipatively synergistic toughened flame-retardant system in the polypropylene matrix. This significantly improves the low-temperature impact toughness of the material while ensuring halogen-free flame-retardant efficiency.

[0078] Comparative Example 1 used commercially available ammonium polyphosphate instead of cerium-loaded polydopamine-coated ammonium polyphosphate flame retardant. Its flammability rating dropped to V-1, and its maximum smoke density and low-temperature impact resistance were significantly inferior to the example. This may be because commercially available ammonium polyphosphate is a rigid inorganic particle lacking a polydopamine organic coating layer on its surface. The large difference in modulus between it and the polypropylene matrix exacerbates interfacial stress concentration at low temperatures. Furthermore, the lack of polydopamine anchoring points in the system prevents the eugenol-modified polysiloxane from being directionally enriched on the particle surface, hindering the effective interfacial compliance effect. Additionally, the absence of polydopamine char-forming synergy and cerium-catalyzed graphitization results in insufficient carbon layer density, leading to a decrease in the flame retardancy rating and an increase in smoke production.

[0079] Comparative Example 2 uses polydopamine-coated ammonium polyphosphate instead of cerium-loaded polydopamine-coated ammonium polyphosphate flame retardant. Its mechanical and low-temperature impact resistance properties are comparable to those of Example 2, but the maximum smoke density is significantly higher. This may be because cerium was not introduced into the system, resulting in the lack of catalytic densification of the char layer during combustion, insufficient high-temperature stability of the char layer, and the inability to catalytically oxidize combustible gases such as CO, leading to increased smoke release and a decrease in the smoke-blocking effect of the material.

[0080] Comparative Example 3 used commercially available hydrogen-terminated silicone oil instead of eugenol-modified polysiloxane. Its room-temperature notched impact strength was lower than that of the example, and the decrease in low-temperature notched impact strength was more pronounced. This may be because the hydrogen-terminated silicone oil molecular chain does not contain polar functional groups such as phenolic hydroxyl groups at its ends, making it unable to form hydrogen bonds with the polydopamine coating layer. Its interfacial enrichment on the flame-retardant particle surface is limited. At room temperature, the polypropylene matrix and ethylene-octene copolymer rubber phase can still bear the main stress dissipation, and the impact of insufficient interfacial enrichment is relatively limited. However, at low temperatures, the lack of anchored low-temperature compliant segments at the interface for stress relaxation means that modulus mismatch cannot be effectively alleviated, and cracks easily initiate and propagate along the interface, leading to a significant decrease in low-temperature impact resistance.

[0081] Comparative Example 4, which did not include eugenol-modified polysiloxane and was replaced with an equal amount of block copolymer polypropylene, exhibited inferior low-temperature impact resistance and low-temperature drop hammer impact resistance compared to the Example. This may be due to the lack of a flexible interface buffer layer on the surface of the flame-retardant particles in the system. Under low-temperature conditions, the modulus mismatch between the matrix and rigid particles is amplified, and the impact stress cannot be dissipated through the interface layer. When the pipe wall is subjected to external force impact, microcracks are easily generated, resulting in a decrease in the material's performance.

[0082] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention.

Claims

1. A halogen-free flame-retardant polypropylene material, characterized in that, The following raw materials are included by weight: 300-500 parts of polypropylene resin; 30-60 parts of ethylene-octene copolymer; 10-20 parts of maleic anhydride-grafted polypropylene; Eugenol-modified polysiloxane 10-25 parts; 40-60 parts of cerium-loaded polydopamine-coated ammonium polyphosphate flame retardant; Antioxidant 1010: 0.5-1 part; Antioxidant 168, 0.5-1 part; Calcium stearate 1-3 parts.

2. The halogen-free flame-retardant polypropylene material according to claim 1, characterized in that, The specific preparation process of the halogen-free flame-retardant polypropylene material is as follows: Polypropylene resin, ethylene-octene copolymer, maleic anhydride-grafted polypropylene, cerium-loaded polydopamine-coated ammonium polyphosphate flame retardant, antioxidant 1010, antioxidant 168 and calcium stearate are placed in a mixer and mixed at 300-500 r / min for 5-10 min. The mixed material is then fed into a twin-screw extruder through the main feed port. Eugenol-modified polysiloxane is injected through the side feed port. After melt blending and extrusion, the material is cooled and pelletized to obtain halogen-free flame-retardant polypropylene material.

3. The halogen-free flame-retardant polypropylene material according to claim 2, characterized in that, The twin-screw extruder has four sections with temperature settings of 170-180℃, 180-190℃, 190-200℃, 195-205℃, a die head temperature of 190-200℃, and a screw speed of 200-300 r / min.

4. The halogen-free flame-retardant polypropylene material according to claim 3, characterized in that, The specific preparation process of the eugenol-modified polysiloxane is as follows: Hydrogen-containing silicone oil and eugenol were placed in a reactor equipped with a condenser and stirred at 25-35℃ for 10-20 min. Karstedt platinum catalyst was added under a nitrogen atmosphere, and the temperature was raised to 90-100℃ for 6-8 h. The reaction solution was then distilled under reduced pressure to constant weight to obtain eugenol-modified polysiloxane.

5. The halogen-free flame-retardant polypropylene material according to claim 4, characterized in that, The ratio of the hydrogen-containing silicone oil, eugenol and Karstedt platinum catalyst is 20-40g: 2-4g: 0.1-0.2mL.

6. The halogen-free flame-retardant polypropylene material according to claim 2, characterized in that, The specific preparation process of the cerium-supported polydopamine-coated ammonium polyphosphate flame retardant is as follows: Cerium nitrate hexahydrate, anhydrous ethanol, and deionized water were placed in a reaction vessel and stirred at 25-35℃ for 40-60 min. Polydopamine-coated ammonium polyphosphate was added and stirred at 40-45℃ for 1-2 h. Ammonia water with a concentration of 1 mol / L was added to adjust the pH of the reaction solution to 9.0-10.5, and stirring was continued for 1-2 h. The mixture was allowed to stand at 45-55℃ for 6-8 h, filtered, washed, and freeze-dried to constant weight to obtain cerium-loaded polydopamine-coated ammonium polyphosphate flame retardant.

7. The halogen-free flame-retardant polypropylene material according to claim 6, characterized in that, The ratio of cerium nitrate hexahydrate, anhydrous ethanol, deionized water, and polydopamine-coated ammonium polyphosphate is 35-50g: 200-300mL: 1-1.5L: 60-80g.

8. The halogen-free flame-retardant polypropylene material according to claim 7, characterized in that, The specific preparation process of the polydopamine-coated ammonium polyphosphate is as follows: Dopamine hydrochloride, ammonium polyphosphate, and deionized water were placed in a reaction vessel and stirred at 25-35℃ for 10-20 min. A Tris-HCl buffer solution with a pH of 8.5 was added, and a sodium hydroxide solution with a concentration of 0.5 mol / L was added to adjust the pH of the reaction solution to 8.5-9.

0. The reaction was carried out at 20-30℃ for 22-24 h. The mixture was then centrifuged, washed, and vacuum dried to constant weight to obtain polydopamine-coated ammonium polyphosphate. The ratio of the amount of dopamine hydrochloride, ammonium polyphosphate, deionized water and Tris-HCl buffer solution is 20-25g: 80-100g: 1-1.2L: 80-120mL.

9. The application of a halogen-free flame-retardant polypropylene material as described in any one of claims 1-8 in water supply and drainage pipes, characterized in that, The water supply and drainage pipe is made of halogen-free flame-retardant polypropylene material, which is melted and plasticized by a single screw extruder and extruded into a pipe blank by the die head. The pipe blank is then subjected to vacuum sizing, spray cooling, traction and cutting in sequence.

10. The application according to claim 9, characterized in that, The single-screw extruder has four sections with temperature settings of 170-180℃, 180-190℃, 190-200℃, and 195-205℃, respectively. The die head temperature is 190-200℃, and the screw speed is 30-50 r / min.

Citation Information

Patent Citations

  • Halogen-free flame-retardant polypropylene pipe and preparation method thereof

    CN114410008A